Pernikahan Semarga Bagi Masyarakat Lamaholot dalam Perspektif Hukum Islam - Hidayatullah Ratuloly; Muhammad Akil; Said Syarifuddin (Universitas Muslim Indonesia, 2021)
In the customary law of Lamaholot concerning the prohibition of marriages that are patrilineal in nature or draw a lineage from the father, it is called